2014
DOI: 10.1182/blood.v124.21.1765.1765
|View full text |Cite
|
Sign up to set email alerts
|

Obinutuzumab (GA101) Is Less Prone to Antagonism of Immune Effector Function By Ibrutinib Than Rituximab in Vitro and in Vivo

Abstract: Introduction: Kohrt et al., Blood, 2014 demonstrated that ibrutinib antagonizes ADCC function of rituximab in vitro in ADCC assays and in vivo in the DHL-4 xenograft model through inhibition of FcgammaR signaling in immune effector cells, possibly mediated by inhibition of ITK. Obinutuzumab (GA101) is a glycoengineered type II CD20 antibody that mediates higher direct cell death induction than rituximab, and by being glycoengineered mediates enhanced induction of ADCC and ADCP. Here we aimed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While the impairment of the ADCC of anti-CD20 mAbs by ibrutinib may be partly due to decreased CD20 expression on the surface of CLL cells [ 23 ], we observed that the enhanced ADCC of Fc- and glycoengineered obinutuzumab was less disturbed by ibrutinib than that of rituximab, similar to ADCC-induced cell lysis as well as NK cell activation and degranulation as surrogate markers in autologous systems [ 24 ]. Also with the second-generation of irreversible BTK inhibitors, the ADCC of obinutuzumab against CLL cells was less impaired than that of rituximab, in agreement with reports about the interference of acalabrutinib or tirabrutinib with the ADCC of anti-CD20 mAbs against Mec1 or SUDHL-4 cells, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 86%
“…While the impairment of the ADCC of anti-CD20 mAbs by ibrutinib may be partly due to decreased CD20 expression on the surface of CLL cells [ 23 ], we observed that the enhanced ADCC of Fc- and glycoengineered obinutuzumab was less disturbed by ibrutinib than that of rituximab, similar to ADCC-induced cell lysis as well as NK cell activation and degranulation as surrogate markers in autologous systems [ 24 ]. Also with the second-generation of irreversible BTK inhibitors, the ADCC of obinutuzumab against CLL cells was less impaired than that of rituximab, in agreement with reports about the interference of acalabrutinib or tirabrutinib with the ADCC of anti-CD20 mAbs against Mec1 or SUDHL-4 cells, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 86%
“…Studies of ibrutinib (the first in class BTK inhibitor) and idelalisib (the first in class PI3k δ inhibitor) in patients with relapsed or refractory CLL have already been published, showing marked efficacy and significant improvements in PFS and OS compared with single-agent type I anti-CD20 mAbs (rituximab or ofatumumab) [Byrd et al 2014; Furman et al 2014]. Interestingly, there was initial concern that ibrutinib antagonized the function of rituximab via reduction of immune effector cell function whereas this inhibitory effect is not observed with obinutuzumab in combination with ibrutinib in in vitro and in vivo studies [Herter et al 2014].…”
Section: Future Directionsmentioning
confidence: 99%